"Delicate and embarassing": U.S. loans to suppress Haitian independence - Mitu Gulati; Kim Oosterlinck; Ugo Panizza; Mark C. Weidemaier (Graduate Institute of International and Development Studies, 2024)
This paper describes George Washington's administration response to a plea for emergency war financing from French colonists who were trying to quash a slave rebellion in Haiti (then Saint Domingue). Washington bypassed Congress and authorized assistance to the French planters, hoping that France would recognize and repay the resulting debt to the United States. The exploration of this episode offers insights on how legal constraints can be overlooked in times of crisis due to political imperatives. On the international law front, it reveals that legal norms perceived as firmly established today were more malleable in the late 18th century. To place the story of U.S. loans and foreign interference in Haiti in historical context, we provide a brief overview of Haiti's independence debt to France and the U.S. loans that led to the American occupation of 1915-1934. Our exploration, primarily sourced from secondary materials, raises more questions than answers. Nonetheless, we hope that by outlining the bare bones of the story and posing pertinent questions, we can inspire further research that digs deeper into this fascinating historical record.
Keywords: N41; F34; K33; H56; 330; Sovereign Debt; Haiti; Emergency War Financing; U.S. Foreign Policy